2019
DOI: 10.1590/s1519-9940200922019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary phytase and various available phosphorus levels on performance and egg quality in Japanese quail

Abstract: SUMMARY Birds show poor utilization of phytic phosphorus in their diets because of the lack of endogenous enzymes to digest phosphorus and make it bioavailable. Therefore, the objective of this study was to evaluate phytase supplementation in the diets of laying quails. Eighty quails were used in a completely randomized experimental design with five treatments and four replicates of four birds each. The treatments were as follows: 0.35% Pd; 0.20% Pd; 0.20% Pd + 500FTUs of phytase; 0.09% Pd; 0.09% Pd + 500 FTUs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In our study, the observed increase in egg shell quality was expected and this might be attributed to the presence of exogenous phytase (a major enzyme component of MXG ® ), which was shown to have a direct influence on the strength and thickness of egg shells in laying birds through increased utilization of calcium and phosphorus (Lima et al, 2011;Rossetto et al, 2019). In addition, Shet, Ghosh, Ajith, Awachat, and Elangovan (2018) suggested the increased phosphorus bioavailability triggered by phytate-phosphorus release as a consequence of phytase activity in the gastrointestinal tract, resulted to greater phosphorus and calcium availability needed to maintain egg weight, shell weight and shell thickness of egg producing birds.…”
Section: Resultsmentioning
confidence: 51%
“…In our study, the observed increase in egg shell quality was expected and this might be attributed to the presence of exogenous phytase (a major enzyme component of MXG ® ), which was shown to have a direct influence on the strength and thickness of egg shells in laying birds through increased utilization of calcium and phosphorus (Lima et al, 2011;Rossetto et al, 2019). In addition, Shet, Ghosh, Ajith, Awachat, and Elangovan (2018) suggested the increased phosphorus bioavailability triggered by phytate-phosphorus release as a consequence of phytase activity in the gastrointestinal tract, resulted to greater phosphorus and calcium availability needed to maintain egg weight, shell weight and shell thickness of egg producing birds.…”
Section: Resultsmentioning
confidence: 51%
“…Additionally, the presence of exogenous phytase (a significant enzyme component of Maxgrain) in the diet may have had a direct impact on the strength and thickness of egg shells in laying chickens through enhanced utilization of calcium and phosphorus in this study's increase in egg shell quality (Lima et al 2011;Rossetto et al 2019). Additionally, Shet et al (2018) found that better phosphorus and calcium availability resulted from increased bioavailability of phosphorus caused by phytatephosphorus release as a result of phytase activity in the gastrointestinal tract, supporting the increase in egg shell quality in favor of the treatment group by revealing that egg-producing birds' egg weight, shell weight, and shell thickness were maintained.…”
Section: Figurementioning
confidence: 98%
“…Japanese quail Fitase feeding of Japanese quail increases the availability of nutrients and growth (Rossetto et al, 2019).…”
mentioning
confidence: 99%